Improving the detailing of atmospheric processes modelling using the Polar WRF model: a case study of a heavy rainfall event at the Akademik Vernadsky station - D. Pishniak; B. Beznoshchenko (Ukrainian Antarctic Journal, 2020)
The Antarctic Peninsula region is of growing interest due to the regional climate change features and related atmospheric circulation patterns. The regional mesoscale atmospheric model Polar Weather Research and Forecasting (WRF) v4.1.1 was used in this research to study a heavy precipitation event over the Ukrainian Antarctic Akademik Vernadsky station region (Antarctic Peninsula). The passage of the cyclone over the Antarctic Peninsula as a typical synoptic process as well as a case of the daily precipitation maximum amount of 2018 were chosen for investigation in this research. The estimation of the modelling quality and downscaling was done by comparing the obtained results with in-situ observation at the Akademik Vernadsky station and cross-domain tracking of average meteorological values and their deviation. The concept of the nested domains allowed to increase the horizontal resolution of the simulated atmosphere up to 1 km and to reproduce the wind regime of this region with high quality. Comparison with measured data showed a significant improvement in wind simulation with increasing of resolution, but worse representation of surface temperature and humidity. The Polar WRF made a general cooling of near surface temperature of 2 °C during the period of simulation and increased precipitation amount by 4.6–8.4 mm (12–21%) on average over the territory relative to the initial data from Global Data Assimilation System. This can be explained by the contribution of noise and imperfection of the model (including static input data of the terrain description). Based on the modelled results, the interaction of wind flow with the mountainous terrain of the Antarctic Peninsula creates a range of complex dynamic effects in the atmosphere. These effects cause local precipitation maxima both over the Peninsula and over the adjacent ocean. These are, respectively, bay-valley areas of increased precipitation and increased precipitation on the crests of shock waves from orographicobstacles. Under certain background wind conditions, the influence of the latter effect can reach the Akademik Vernadsky station and cause the formation of heavy precipitation here.